Combustion characteristics of regenerative heating furnace for oil shale retorting based on top air supply - Yue Yue; Zhu He; Chunhua Wang (Case Studies in Thermal Engineering)
To comply with stricter air pollution standards, a new top air supply technology was proposed. Through numerical simulation, the effects of the number of air nozzles (A), air inclination (B) and fuel gas nozzle position (C) on the average temperature in the furnace, incomplete combustion heat loss and NO emission were analyzed. The research results show that the number of air nozzles has an important impact on the vortex in the pre-combustion chamber, the installation position of the fuel gas nozzles has a certain impact on the vortex formed in the combustion chamber, while the inclination of the air nozzles has no obvious effect on the vortex formation; the mean furnace temperature is most significantly affected by the interaction of factors A and B(A × B), and other factors have relatively little influence; the incomplete combustion heat loss at the exit of the combustion chamber is mainly dominated by factor A, followed by factors A × B and C. For the NO emission value at the exit of the combustion chamber, factors A and A × C have a significant impact, factors A × B also have a certain impact, and other factors can be ignored.